(untitled) (Research, Society and Development, 2020)
Objective: Contextualize through media records, the paths that cross between the nursing’s valorization campaign Nursing Now and the pandemic COVID-19. Method: It is a reflective study, about the daily life of the Nursing Now valorization campaign and the pandemic COVID-19. Results: Different countries have been encouraged to contribute to the valorization of the nursing workforce and to encourage the protagonism process, even in times of global crisis. However, in the course of this global campaign, the life’s these workers and all the world population has been crossed by a pandemic. This form, it is interesting to reflect that political, economic and gender issues continue to influence the training and professional performance. Morover, these crossings have been characterized by impermanence that reflect changes individuals and institutionals actions able of tensioning power relations. Conclusion: The experiences lived by nurses during the pandemic 2020 can contribute to describe the reality of the profession and to design actions of collective interests that attend processes of recognition and professional dignity. In the face of uncertainties, it should be noted that Nursing Now, in fact, needs to continue to be Nursing Now.